Technique for finding design solution for piston compressor with direct gas piston drive under conditions of depletion of the gas reservoir - M. D. Vulf; P. A. Rogov; O. V. Belova; S. V. Goryunov; D. A. Kalinkin (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article discusses approaches for calculation of a piston compressor unit with a direct gas piston drive for the compression of natural gas during long-term production in a depleted gas formation. This task is relevant for gas companies from the standpoint of reducing the cost of gas production. The application of the proposed method allows reducing the final cost of products, which increases the overall profitability of the business